High resolution ancient sedimentary DNA shows that alpine plant diversity is associated with human land use and climate change - Garcés-Pastor, Sandra; Coissac, Eric; Lavergne, Sébastien; Schwörer, Christoph; Theurillat, Jean-Paul; Heintzman, Peter D.; Wangensteen, Owen S.; Tinner, Willy; Rey, Fabian; Heer, Martina; Rutzer, Astrid; Walsh, Kevin; et al. (Nature communications, 2022)
The European Alps are highly rich in species, but their future may be threatened by ongoing changes in human land use and climate. Here, we reconstructed vegetation, temperature, human impact and livestock over the past ~12,000 years from Lake Sulsseewli, based on sedimentary ancient plant and mammal DNA, pollen, spores, chironomids, and microcharcoal. We assembled a highly-complete local DNA reference library (PhyloAlps, 3923 plant taxa), and used this to obtain an exceptionally rich sed aDNA record of 366 plant taxa. Vegetation mainly responded to climate during the early Holocene, while human activity had an additional influence on vegetation from 6 ka onwards. Land-use shifted from episodic grazing during the Neolithic and Bronze Age to agropastoralism in the Middle Ages. Associated human deforestation allowed the coexistence of plant species typically found at different elevational belts, leading to levels of plant richness that characterise the current high diversity of this region. Our findings indicate a positive association between low intensity agropastoral activities and precipitation with the maintenance of the unique subalpine and alpine plant diversity of the European Alps. Here, the authors use sedimentary DNA, pollen, fungal spores, chironomids, and microcharcoal from an alpine lake core to reconstruct vegetation across 12,000 years. They find that vegetation responded to climate in the early Holocene, followed by a shift to human activity from 6000 years onward corresponding with an increase in deforestation and agropastoralism.